Causes of sub-optimal cataract surgical outcomes in patients presenting to a teaching hospital - Kumar, Kshitiz; Gupta, VP; Dhaliwal, U (Nepalese Journal of Ophthalmology, 2012)
Introduction: Surgical treatment for cataract blindness in India is increasing apace; however, sight restoration after surgery is not always satisfactory. Objective: To evaluate visual outcome after cataract surgery and causes of sub-optimal outcome, if any. Materials and methods: A cross-sectional study including the patients who had undergone cataract surgery six months to ten years ago was carried out. The variables studied were visual acuity, demographic and surgical factors and ocular findings. The causes of subnormal outcome was categorized into cataract surgery-related or unrelated. Statistical analysis: SPSS-17 was used; the Chi-square test was used to determine the association between good outcome and categorical variables; the t-test was used for continuous variables. Multivariate analysis using step-wise logistic regression was done. Results: Among 644 patients (644 eyes), good outcome (presenting visual acuity 6/18 or better) after surgery was seen in 266 (41.3 %) eyes. Good outcome was significantly related to urban residence, presence of an intraocular lens and absence of ocular co-morbidities or posterior capsule opacification. Borderline and poor outcomes were mainly due to surgeryrelated causes; treatable causes included uncorrected refractive errors, and posterior capsule opacification. Intra-operative complications resulting in a pulled-up pupil were frequent. Conclusions: Surgical factors are responsible most often for sub-optimal visual outcome; some, like induced astigmatism and vitreous loss, can be modified with training; actively encouraging follow-up visits can allow treatment of residual refractive errors and capsular opacification. DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5855 NEPJOPH 2012; 4(1): 73-79